Penerapan Multi Boezem Dalam Upaya Pengendalian Banjir di Kawasan Industri JIIPE Kabupaten Gresik - Irfan Adiputra Setiawan; Siti Kamilia Aziz; Muhammad Hafiizh Imaaduddiin; Widya Utama (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
The conversion of land use in the JIIPE industrial area covering 1607 hectares has led to increased runoff coefficients and flood discharge. For this reason, flood control infrastructure is required, specifically the construction of boezem in zones 1, 2, and 3. The flood discharge calculations for the river use the HSS Nakayasu method (Q25). For regional flood discharge use the Rational method (Q25). In planning the dimensions and operational patterns of the boezem, it is based on inflow volume, land availability, and water levels of the Mireng River and Lamong Bay. The analysis results show that the storage volume for zone 1 is 120,229.96 m³, for zone 2 is 606,145.29 m³, and for zone 3 is 314,613.06 m³. The pump capacity of zone 1 is 3m3/sec, zone 2 is 10 m3/sec, and zone 3 is 5 m3/sec.